Memahami Hakikat Hukuman Dalam Pendidikan Islam - Sitorus, Azi Shohi; Rahmadani, Nabilla (Ikatan Da'i Indonesia, 2023)
In learning and teaching activities there is a punishment given to students who do not have the attitude of discipline, responsibility and courtesy to their teachers. then such students need to be punished. But giving punishment to students has rules and stages, so before giving punishment an educator must be able to prepare students in accordance with Law Number 2 of 1989. The method used in this study is a qualitative descriptive research method. This analysis is a literature interview which gets data from written materials such as books, magazines, etc. In collecting the data, we used the data which was accepted by using books on Islamic educational philosophy as well as books as well as other related magazines. Punishment cannot be separated from the essence of education, because punishment is always accompanied by a reward. Rewards are designed to increase student interest in learning, while punishment is a preventive measure for students who are not interested in learning.